A superior composite gel polymer electrolyte of Li7La3Zr2O12- poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) for rechargeable solid-state lithium ion batteries. (June 2018) - Liang, Y.F.; Deng, S.J.; Xia, Y.; Wang, X.L.; Xia, X.H.; Wu, J.B.; Gu, C.D.; Tu, J.P.
Graphical abstract: Composite polymer electrolytes PVDF-HFP/LLZO are prepared by a facile combined method and show superior electrochemical performance and remarkably long-term durability. Highlights: Solid electrolyte LLZO dispersed in PVDF-HFP matrix is studied. Garnet inorganic fillers enhance the transport number of Li + . Composite polymer electrolytes show superior electrochemical performance. Coin cells (Li/PVDF-HFP: LLZO/LiFePO4 ) show good cycling performance. Abstract: High-quality solid electrolyte is essential for the growing need of lithium ion batteries. Herein, we report a novel organic-inorganic composite electrolyte based on Li7 La3 Zr2 O12 ceramic powder incorporated into PVDF-HFP through a simple combined method. At room temperature, the composite polymer electrolyte (CPE) possesses a good ionic transmission improvement of 3.71 × 10 −4  S cm −1 . The CPE behaves a fine lithium ion transference number of 0.58 and an electrochemical window of up to 4.65 V. CPEs display meliorative electrochemical stability compared to pure PVDF-HFP electrolyte. The cathode presents an excellent initial discharge capacity of 163.1 mAh g −1 at 0.2 C in Li/CPE/LiFePO4 cell. The cell with CPE displays much better capacity retention than that with pure PVDF-HFP electrolyte. The Li7 La3 Zr2 O12 modified PVDF-HFP is a promising electrolyte for lithium ion batteries.